Surgical Versus Conservative Treatments for Displaced Midshaft Clavicular Fractures. Issue 26 (July 2015) - Zhao, Jia-Guo; Wang, Jia; Long, Lei; Harris., Kevin
<x xml:space="preserve">Abstract</x> Abstract Multiple meta-analyses have been performed to compare surgical and conservative interventions for treating displaced midshaft clavicular fractures. But conclusions are discordant. The purposes of current study were (1) to conduct a systematic review of meta-analyses comparing surgical and conservative interventions for the treatment of displaced midshaft clavicular fractures, (2) to help decision makers interpret and choose among discordant meta-analyses, and (3) to provide treatment recommendations through the best available evidence. We searched the Cochrane library, PubMed, and EMBASE databases to identify meta-analyses comparing surgical and conservative treatments for the displaced midshaft clavicular fractures. Two investigators independently scanned titles and abstracts to exclude irrelevant articles and identify meta-analyses that met the eligibility criteria. The methodological quality of the meta-analysis was independently assessed by the two investigators using the Oxford Centre for Evidence-based Medicine Levels of Evidence and the Assessment of Multiple Systematic Reviews (AMSTAR) tool. The Jadad decision algorithm was applied to determine which of the included studies provided the best available evidence. Six meta-analyses met the eligibility criteria in this systematic review. AMSTAR scores ranged from 5 to 10. The Jadad decision-making tool suggests that the highest quality review should be selected based on the publication characteristics of the primary trials, the methodology of the primary trials, the language restrictions, and whether analysis of data on individual patients was included in the study. As a result, we selected a high-quality Cochrane review. This systematic review of overlapping meta-analyses comparing surgical and conservative treatments suggests that surgical treatment provides a lower rate of overall treatment failure and a better functional outcome, but is associated with more implant-related complications. Hence, treatment should be individualized, with careful consideration of the advantages and disadvantages of each treatment method and of patient preferences.